Ibn Hisham al-Lakhmi and his guidance in substitution and the movement of the structure of words in his response to Ibn Makki al-Siqilli - Balkhair, Ahmed (Al-Adab Journal, 2023)
This research is concerning about the phonetic guidance of Ibn Hisham Al Lakhmi in his Book (Al Madkhal Ila tagweem Al Lisan wo Ta’aleem Al Bayan) in which he replied to Ibn Makki Al Saggali’s book (Tathgeef Al Lisan Wo Talgeeh Al Jenan), where Ibn Makki characterizes the Arabic Language situation in Sicilia during the 6th Hijri century, he mistaken the public in his era and consider them have mistaken the way to exercise it. In a reply to Ibn Makki, Ibn Hisham pointed out; whatever has been considered as a distortion by Ibn Makki in fact wasn’t true, and described Ibn Makki’s statements as an illusion. The aim of this research is to point out the Arabic language’s phonetic phenomenons of Sicilia’s people during the 6th Hijri century, through what has been stated by Ibn Hisham in the above-mentioned book and to know his stand from the opinion of Ibn Makki regarding those phonetic phenomenons.